Sine-square Embedded Fuzzy Sets - Karakose, Mehmet (Ieee, 2010)
Type-2 fuzzy sets minimize the effects of uncertainties that cannot be modeled using type-l fuzzy sets. However, the computational complexity of the type-2 fuzzy sets is very large and it is more difficult to use and understand than are type-l fuzzy sets. This paper proposes sine-square embedded fuzzy sets and gives a comparison with type-2 and nonstationary fuzzy sets. The sine-square embedded fuzzy sets consist of type-l fuzzy sets and sine function. The footprint of uncertainty in the type-2 fuzzy sets is provided with amplitude and frequency of sine-square function in the proposed algorithm. The proposed sine-square embedded fuzzy sets are very simpler than the type-2 fuzzy sets and the nonstationary fuzzy sets. Finally, the simulation results are carried out to demonstrate the effectiveness of the proposed fuzzy sets.
IEEE International Conference on Systems, Man and Cybernetics -- OCT 10-13, 2010 -- Istanbul, TURKEY
Keywords: fuzzy set; sine-square set; type-2 fuzzy set; membership function; nonstationary fuzzy set